A Conceptual Research of Training Effectiveness, Attitude, and Commitment on Food Safety Behavior in Home-Based Businesses - Shatha Ali AL MUA'LLA; Bader Yousef OBEIDAT; Ra’ed MASA'DEH (Communications of International Proceedings, 2020)
As, the food safety behavior in the home-based business (HBB) is a concept that has not been given sufficient attention regarding training effectiveness, attitudes and commitment the evaluation of practices to achieve business success in the realization of the important food safety, and since there are fewer researches have been done in the area of HBB. Therefore, this research comes in to measure the effect of the training effectiveness, commitment, and attitude into food safety behavior that can be realized especially in the home-based businesses that serve the interest of the local communities in any given place. A quantitative deductive approach will be conducted to test the model, the research variable, and the outcomes for difference HBB within UAE. The research expects results will be a significant correlation between the food safety behavior variables, training effectiveness variables, commitment variables, and attitude variables, as well as thus developing a conclusion adoptable by the different governments, and other stakeholders may apply in the industry to create a higher value regarding food safety behavior.
Keywords: Food Safety Behavior; Training Effectiveness; Commitment; Attitude.